Quantifying baseline costs and cataloging potential optimization strategies for kelp aquaculture carbon dioxide removal - Coleman, Struan; Dewhurst, Tobias; Fredriksson, David W.; St. Gelais, Adam T.; Cole, Kelly L.; MacNicoll, Michael; Laufer, Eric; Brady, Damian C. (Frontiers in Marine Science, 2022)
To keep global surface warming below 1.5°C by 2100, the portfolio of cost-effective CDR technologies must expand. To evaluate the potential of macroalgae CDR, we developed a kelp aquaculture bio-techno-economic model in which large quantities of kelp would be farmed at an offshore site, transported to a deep water “sink site”, and then deposited below the sequestration horizon (1,000 m). We estimated the costs and associated emissions of nursery production, permitting, farm construction, ocean cultivation, biomass transport, and Monitoring, Reporting, and Verification (MRV) for a 1,000 acre (405 ha) “baseline” project located in the Gulf of Maine, USA. The baseline kelp CDR model applies current systems of kelp cultivation to deep water (100 m) exposed sites using best available modeling methods. We calculated the levelized unit costs of CO2eq sequestration (LCOC; tCO2eq-1). Under baseline assumptions, LCOC was 17,048 tCO2eq-1. Despite annually sequestering 628 tCO2eq within kelp biomass at the sink site, the project was only able to net 244 C credits (tCO2eq) each year, a true sequestration “additionality” rate (AR) of 39% (i.e., the ratio of net C credits produced to gross C sequestered within kelp biomass). As a result of optimizing 18 key parameters for which we identified a range within the literature, LCOC fell to 1,257 tCO2eq-1 and AR increased to 91%, demonstrating that substantial cost reductions could be achieved through process improvement and decarbonization of production supply chains. Kelp CDR may be limited by high production costs and energy intensive operations, as well as MRV uncertainty. To resolve these challenges, R&D must (1) de-risk farm designs that maximize lease space, (2) automate the seeding and harvest processes, (3) leverage selective breeding to increase yields, (4) assess the cost-benefit of gametophyte nursery culture as both a platform for selective breeding and driver of operating cost reductions, (5) decarbonize equipment supply chains, energy usage, and ocean cultivation by sourcing electricity from renewables and employing low GHG impact materials with long lifespans, and (6) develop low-cost and accurate MRV techniques for ocean-based CDR.